Analisis Indikator Proses Berfikir Kreatif dalam Rencana Pelaksanaan Pembelajaran (RPP) IPA di Kelas IV Madrasah Ibtidaiyah Terpadu As-Salam Ambon - Mohd - Syafit; Anasufi - Banawi; Siti - Nurjanah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT. This study aims to (1) analyze teachers’ lesson plans in developing students' creative thinking skills at Madrasah Ibtidaiyah (MI – Islamic Primary School), and (2) investigate the obstacles faced by teachers in carrying out assessments of learning outcomes that develop students' creative thinking skills at science subjects. This research uses a descriptive method. The research subjects consisted of 3 teachers and 4 (2 boys and 2 girls) fourth grade students at the Integrated Islamic School (Madrasah Ibtidaiyah Terpadu - MIT) As-Salam Ambon in the even semester of Academic Year 2021/2022. The research instruments consisted of lesson plan analysis sheets, observation sheets, interview guidelines, and documentation. Lesson plan analysis was conducted using an assessment rubric, and observation data related to the emergence of 13 indicators of creative thinking during classroom instruction are then summarized in a table of frequency, average, and percentage. The results of the study show that the emergence of creative thinking indicators is 9 (69.23%) in Teacher 1's lesson plan, 11 (84.62%) in Teacher 2’s plan, and 12 (92.31%) in Teacher 3's plan. The average emergence of creative thinking indicators is 10.67 (82.07%), classified as good. There is a match between the lesson plans developed by the teachers and the indicators of creative thinking. The suitability of the content of the lesson plans is also seen from the implementation and assessment, with an average percentage of learning implementation of 96.43% classified as very good. The obstacles faced by teachers are limited time of classroom instruction and the application of an assessment that contains three domains at once. From these results, it is suggested to strengthen teachers' skill in developing lesson plans through similar training and research with more respondents.Keywords: Analysis, indicator, creative thinking process, lesson plan, science, madrasah ibtidaiyah